Which Skills Do Students with Intellectual Disabilities Need for Pursuing Leisure Activities After Graduation? A Survey among Vocational Rehabilitation Practitioners in Japan - Yamada, Yukiya; Maebara, Kazuaki (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
Background: Leisure activities contribute to the quality of life and continuation of employment for individuals with disabilities. However, education related to leisure activities is inadequate in special needs schools in Japan. Purpose: This study aimed to clarify which components of leisure guidance are considered important by vocational rehabilitation practitioners in Japan. Methods: An online survey was conducted in 337 branches of the Support Center for Employment and Livelihood of Persons with Disabilities in Japan. Results: Employment support practitioners recognized the importance of teaching students how to use their leisure time outside of working hours and helping them cultivate skills necessary to engage in leisure activities, regardless of whether they were still in school or had already graduated. In school, importance was placed on providing activities aimed at expanding leisure opportunities after graduation. For the period after graduation, the emphasis shifted to acquiring specific abilities necessary for engaging in leisure activities with other people, such as money management and securing means of transportation. Conclusion: This study provides a direction for optimizing the quality of leisure guidance for individuals with special needs. The findings can help improve teaching practices in special needs schools and enhance the effectiveness of transition support for students with disabilities.